2023
DOI: 10.1177/03000605231182558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-flow nasal cannula oxygen therapy for patients with acute exacerbation of chronic obstructive pulmonary disease in combination with type II respiratory failure

Abstract: Objective To evaluate the therapeutic effects of high-flow nasal cannula (HFNC) oxygen therapy in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and type II respiratory failure. Methods Seventy-two patients with AECOPD and type II respiratory failure were randomly allocated to an HFNC oxygen therapy trial group or a non-invasive positive-pressure ventilator therapy (NIPPV) control group. Their arterial blood gas parameters and comfort, evaluated using a questionnaire, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Aiming Liu et al showed that HFNC has a good therapeutic effect in patients with AECOPD and type II respi-ratory failure. It improves the blood gas parameters, patient comfort and has clinical value [ 5 ]. HFNC has become a go-to solution for managing acute hypoxic respiratory failure in children and in averting reintubation post-extubation.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming Liu et al showed that HFNC has a good therapeutic effect in patients with AECOPD and type II respi-ratory failure. It improves the blood gas parameters, patient comfort and has clinical value [ 5 ]. HFNC has become a go-to solution for managing acute hypoxic respiratory failure in children and in averting reintubation post-extubation.…”
Section: Introductionmentioning
confidence: 99%